Anteprojeto de reforma e adaptação do Centro de Reabilitação Social no Pará - YOSHIKAWA, Leticia Kimie (2023)
This work proposes an architectural adaptation for the Kosei Home Social Rehabilitation Center, in Ananindeua / PA, which assist the elderly immigrants from the Japanese community in the region. It started from the analysis of the importance of the community and its current needs in relation to the Center, considering its importance among the Nipponians for the specific care given to the community. Therefore, it was identified the need for some adjustments, adaptations and extensions. The work begins with the development of a bibliographic research about the care with the elderly and the functioning of Nursing Home. In the course of the work, there was a need for greater attention to accessibility requirements that are fundamental to this type of space. In addition, the architectural proposal presented is based on the parameters of environmental, thermal, lighting and acoustic comfort, where strategies are applied for the best use of natural light, ventilation and acoustic treatment for the best performance of the space and its adaptation to use